Organizational Barriers to Technology Adoption: Evidence from Soccer-Ball Producers in Pakistan - David Atkin; Azam Chaudhry; Shamyla Chaudry; Amit K. Khandelwal; Eric Verhoogen (Institute for the Study of Labor (IZA), 2015)
This paper studies technology adoption in a cluster of soccer-ball producers in Sialkot, Pakistan. We invented a new cutting technology that reduces waste of the primary raw material and gave the technology to a random subset of producers. Despite the arguably unambiguous net benefits of the technology for nearly all firms, after 15 months take-up remained puzzlingly low. We hypothesize that an important reason for the lack of adoption is a misalignment of incentives within firms: the key employees (cutters and printers) are typically paid piece rates, with no incentive to reduce waste, and the new technology slows them down, at least initially. Fearing reductions in their effective wage, employees resist adoption in various ways, including by misinforming owners about the value of the technology. To investigate this hypothesis, we implemented a second experiment among the firms that originally received the technology: we offered one cutter and one printer per firm a lump-sum payment, approximately equal to a monthly wage, conditional on them demonstrating competence in using the technology in the presence of the owner. This incentive payment, small from the point of view of the firm, had a significant positive effect on adoption. We interpret the results as supportive of the hypothesis that misalignment of incentives within firms is an important barrier to technology adoption in our setting.
Keywords: O1; O3; D2; L2; 330; technology adoption; organizations; manufacturing firms; Pakistan; soccer balls